Immunomodulatory effects of low dose chemotherapy and perspectives of combanation with immunotherapy - Nars, Mariana de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Nowadays cancer is one of the main causes of death and many efforts worldwide have been driven to find out new treatments and approaches in order to extinguish or reduce this group of disorder. Chemotherapy is the main treatment for cancer, however, conventional schedule based on maximum tolerated dose (MTD) show several side effects and frequently allow the development of drug resistance. In this review we present the evidence that metronomic chemotherapy, based on the frequent administration of low or intermediate doses of chemotherapeutics is as efficient as MTD and works better in some situations. Finally, we present some data indicating that noncytotoxic concentrations of antineoplastic agents are able to both up-regulate the immune system and increase the susceptibility of tumor cells to cytotoxic T lymphocytes. Taken together, data from the literature provide us the evidence that low concentrations of selected chemotherapeutics agents, rather than conventional high doses, should be chosen for combination with immunotherapy

Não disponível
Keywords: Quimioterapia; Imunoterapia; Vacinas; Celulas que apresentam antigenos; Celulas T